2011
DOI: 10.1111/j.1365-2486.2011.02606.x
|View full text |Cite
|
Sign up to set email alerts
|

Recent climate changes interact with stand structure and management to determine changes in tree carbon stocks in Spanish forests

Abstract: Most temperate forests are accumulating carbon (C) and may continue to do so in the near future. However, the situation may be different in water-limited ecosystems, where the potentially positive effects of C and N fertilization and rising temperatures interact with water availability. In this study, we use the extensive network of plots of two consecutive Spanish national forest inventories to identify the factors that determine the spatial variation of the C stock change, growth, and mortality rate of fores… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

13
108
3
13

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 134 publications
(137 citation statements)
references
References 44 publications
13
108
3
13
Order By: Relevance
“…Our results suggest that a lower precipitation could reduce potential carbon stocks in lowland pines but could be beneficial for P. uncinata growing in high altitudes. In line with this result, Vayreda et al (2012b) identified reductions on carbon accumulations in Spanish forests due to recent warming and due to lower water availability. Using the STLs, we can identify which species are likely to grow to larger sizes under new conditions and promote these species as a climate change adaptation strategy.…”
Section: Discussionsupporting
confidence: 72%
“…Our results suggest that a lower precipitation could reduce potential carbon stocks in lowland pines but could be beneficial for P. uncinata growing in high altitudes. In line with this result, Vayreda et al (2012b) identified reductions on carbon accumulations in Spanish forests due to recent warming and due to lower water availability. Using the STLs, we can identify which species are likely to grow to larger sizes under new conditions and promote these species as a climate change adaptation strategy.…”
Section: Discussionsupporting
confidence: 72%
“…These key characteristics, together with the frequent occurrence of disturbances such as fire or pests, have influenced the composition, structure and functioning of these forest ecosystems. Hence, in order to maintain the level of ecosystem services in this area, forest management is required, particularly in the light of reports that climate change is causing a reduction in the carbon sink capacity of unmanaged Spanish forests due to lower water availability (Vayreda et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…temperatura o precipitación) en el periodo de estudio respecto al clima medio observado en un periodo de referencia (e.g. Vayreda et al 2012; Ruiz-Benito et al datos sin publicar). Por otra parte, la correlación entre series dendrocronológicas estandarizadas de crecimiento radial y series de variables climáticas para las especies puede usarse como un indicador de la sensibilidad climática de las mismas (e.g.…”
Section: Aplicación De Modelos Para La Evaluación De La Vulnerabilidaunclassified
“…interacciones entre el clima y la competencia) que pueden causar efectos no proporcionales sobre los diferentes componentes de la sensibilidad de las especies como la productividad o la mortalidad (e.g. Linares et al 2010;Vayreda et al 2012;Ruiz-Benito et al 2013b). Además, otros procesos pueden causar importantes modificaciones en la abundancia y distribución de especies, desde por ejemplo interacciones planta-suelo (McCarthy-Neumann e Ibáñez, 2012), procesos a diferentes niveles tróficos (Harrington et al 1999) o efectos competitivos especie-específicos (Gomez-Aparicio et al 2011); hasta posibles cambios en la frecuencia e intensidad del ré-gimen de incendios (Pausas 2004;Pausas et al 2008) o cambios en el uso del suelo (Thuiller et al 2008).…”
Section: Conclusionesunclassified